The art of forging neurons: Direct reprogramming of somatic cells into induced neuronal cells Die kunst des neuronenschmiedens: Direkte reprogrammierung somatischer zellen in induzierte neuronale zellen - Karow, Marisa; Berninger, Benedikt (Neuroforum, 2013)
Cellular reprogramming has shed new light on the plasticity of terminally differentiated cells and discloses novel strategies for cell-based therapies for neurological disorders. With accumulating knowledge of the programs underlying the genesis of the distinct neural cell types, especially with the identification of relevant transcription factors and microRNAs, reprogramming of somatic cells of different origins into induced neuronal cells or neural stem cells has been successfully achieved. Starting with the general concept of reprogramming we discuss here three different paradigms: 1) direct conversion of CNS-foreign cells such as skin fibroblasts into induced neuronal cells or neural stem cells; 2) transdifferentiation of CNS resident cells such as astrocytes and brain pericytes into induced neuronal cells; 3) reprogramming of one neuronal subtype into another. The latter has already been successfully achieved in vivo during early brain development, providing strong impulse for the attempt to succeed in direct reprogramming in situ for future brain repair. © Springer-Verlag GmbH 2013.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Astrocytes; Cell-based therapy; Lineage reprogramming; Pericytes; Transdifferentiation